2023
DOI: 10.5114/hpc.2022.122344
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcomes of Diabetes Among Covid-19 Patients in Duhok Covid-19 Health Facilities: A Cross-Sectional Study

Abstract: Background. The objectives of this study were to determine the prevalence of type 2 diabetes mellitus (T2DM) among patients with COVID-19, examining the relationship between COVID-19 severity and T2DM in hospitalized patients, detecting T2DM outcomes in COVID-19 patients, and identifying the vaccination rates of COVID-19 patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, other data are supportive of this aforementioned view because they show that there does appear to be a high rate of deficient vitamin D levels in the acute or post-COVID-19 studied groups although this is not well correlated or consistent. [27][28][29][30][31][32] Carpagnano et al, 33 found 81% of their COVID-19 cases to be vitamin D deficient, and patients with a severe vitamin D deficiency reportedly had a 50% chance of dying, while those with adequate vitamin D levels, had lower death rates at 10 days.…”
Section: Key Findingsmentioning
confidence: 99%
“…However, other data are supportive of this aforementioned view because they show that there does appear to be a high rate of deficient vitamin D levels in the acute or post-COVID-19 studied groups although this is not well correlated or consistent. [27][28][29][30][31][32] Carpagnano et al, 33 found 81% of their COVID-19 cases to be vitamin D deficient, and patients with a severe vitamin D deficiency reportedly had a 50% chance of dying, while those with adequate vitamin D levels, had lower death rates at 10 days.…”
Section: Key Findingsmentioning
confidence: 99%
“…However, other data are supportive of this aforementioned view because they show that there does appear to be a high rate of deficient vitamin D levels in the acute or post-COVID-19 studied groups although this is not well correlated or consistent. [27][28][29][30][31][32] Carpagnano et al, 33 found 81% of their COVID-19 cases to be vitamin D deficient, and patients with a severe vitamin D deficiency reportedly had a 50% chance of dying, while those with adequate vitamin D levels, had lower death rates at 10 days.…”
Section: Key Findingsmentioning
confidence: 99%